The Impact of Employment Status, Income, and Occupation on the Association Between Workplace Benefits and Health‐Related Work Absences - Stimpson, Jim P.; Billig, Jessica; Gurley, Tami; Liao, Joshua M. (American journal of industrial medicine, 2025)
ABSTRACT Background Workplace benefits such as paid sick leave and employer‐sponsored health insurance influence workers' ability to take time off when ill or injured. We examined whether and to what extent these workplace benefits complement each other in affecting health‐related work absences, and whether associations varied by employment status, income, and occupation. Methods This cross‐sectional study analyzed pooled data from the 2021 and 2023 National Health Interview Survey (NHIS), a nationally representative survey of US adults. The sample included 31,280 employed adults. Workers were classified into four workplace benefits groups: paid sick leave only, employer‐sponsored health insurance only, both benefits, and neither benefit. The primary outcome was health‐related work absence in the past 12 months. Interaction terms assessed differences in probability of absence by employment status (full‐time vs. part‐time), income (< 400% vs. ≥ 400% of the federal poverty level), and occupation type (Management, Professional, Service, Sales, and Production). Results Compared to those with neither benefit, the probability of work absence was 7.3 points higher with employer‐sponsored health insurance only (p < 0.001), 4.6 points higher with paid sick leave only (p = 0.002), and 12.0 points higher with both benefits (p < 0.001). The association between workplace benefits and health‐related work absence varied by employment status, income level, and occupation type (p < 0.001 for all interactions). Conclusions Access to paid sick leave and health insurance increased the likelihood of taking time off due to illness or injury, with differences by employment status, income, and occupation.